Pendampingan Kedisiplinan Peserta Didik Melalui Pembiasaan Sholat Berjamaah di PKBM PNF KBRI Kuala Lumpur - Khoirul Anam; Qurroti A yun; Moch Mahsun; Nurhafid Ishari (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
This mentoring aims to describe the implementation of student discipline mentoring through congregational prayer habits at the Indonesian Embassy's PNF Community Learning Center (PKBM PNF) in Kuala Lumpur and analyze its influence on the formation of religious character. The problem lies in the low consistency of students in performing congregational prayers, especially outside of school. The method used is service learning, involving the supervising teacher, students, and the principal as the subjects of the activity. The results show that the habit of congregational prayer is carried out routinely every day and has become part of the school culture. This program not only forms the habit of regular worship but also instills religious values ​​such as time discipline, togetherness, and a sense of responsibility for spiritual obligations. In addition to being a worship routine, this activity serves as a means of character formation that is integrated into the educational process. The support of the school environment and the example of teachers also play an important role in maintaining the consistency of this habit. Thus, mentoring through congregational prayer habits has proven effective in improving discipline and strengthening the religious character of students at the Indonesian Embassy's PNF Community Learning Center (PKBM PNF) in Kuala Lumpur.